Longitudinal patterns in indeterminate HIV rapid antibody test results: a population-based, prospective cohort study - Joanne H. Hunt; George Mwinnyaa; Eshan U. Patel; M. Kate Grabowski; Joseph Kagaayi; Ronald H. Gray; Joseph Ssekasanvu; Maria J. Wawer; Godfrey Kigozi; Larry W. Chang; Sarah Kalibbala; Margaret Nakalanzi; et al. (Microbiology Spectrum, 2024)
ABSTRACT Rapid HIV tests are critical to HIV surveillance and universal testing and treatment programs. We assessed longitudinal patterns in indeterminate HIV rapid test results in an African population-based cohort. Prospective HIV rapid antibody test results, defined by two parallel rapid tests, among participants aged 15–49 years from three survey rounds of the Rakai Community Cohort Study, Uganda, from 2013 to 2018, were assessed. An indeterminate result was defined as any weak positive result or when one test was negative and the other was positive. A total of 31,405 participants contributed 54,459 person-visits, with 15,713 participants contributing multiple visits and 7,351 participants contributing 3 visits. The prevalence of indeterminate results was 2.7% (1,490/54,469). Of the participants with multiple visits who initially tested indeterminate (n = 591), 40.4% were negative, 18.6% were positive, and 41.0% were indeterminate at the subsequent visit. Of the participants with two consecutive indeterminate results who had a third visit (n = 67), 20.9% were negative, 9.0% were positive, and 70.2% remained indeterminate. Compared to a prior negative result, a prior indeterminate result was strongly associated with a subsequent indeterminate result [adjusted prevalence ratio, 23.0 (95% CI = 20.0–26.5)]. Compared to men, women were more likely to test indeterminate than negative [adjusted odds ratio, 2.3 (95% CI = 2.0–2.6)]. Indeterminate rapid HIV test results are highly correlated within an individual and 0.6% of the population persistently tested indeterminate over the study period. A substantial fraction of people with an indeterminate result subsequently tested HIV positive at the next visit, underscoring the importance of follow-up HIV testing protocols.IMPORTANCERapid HIV tests are a critical tool for expanding HIV testing and treatment to end the HIV epidemic. The interpretation and management of indeterminate rapid HIV test results pose a unique challenge for connecting all people living with HIV to the necessary care and treatment. Indeterminate rapid HIV test results are characterized by any weak positive result or discordant results (when one test is negative and the other is positive). We systematically tested all participants of a Ugandan population-based, longitudinal cohort study regardless of prior test results or HIV status to quantify longitudinal patterns in rapid HIV test results. We found that a substantial fraction (>15%) of participants with indeterminate rapid test results subsequently tested positive upon follow-up testing at the next visit. Our findings demonstrate the importance of follow-up HIV testing protocols for indeterminate rapid HIV test results.